Preventing Partner Violence: Research and Evidence-Based Intervention Strategies. 2009
DOI: 10.1037/11873-010
|View full text |Cite
|
Sign up to set email alerts
|

Criminal justice responses to partner violence: History, evaluation, and lessons learned.

Abstract: In this chapter, we briefly review the history of partner violence in legislation, policing, prosecution, and more recent alternatives to the traditional court process. We then describe the little that is known about the effectiveness of criminal justice responses to partner violence over the past half century. We draw on lessons learned from interventions for other forms of criminal conduct. We take the position that this field embodies some challenges for psychologists and researchers. First, most criminal j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 85 publications
1
5
0
Order By: Relevance
“…Even with a relatively low base rate for physical assault recidivism, the ODARA total score was still able to accurately discriminate between recidivists and nonrecidivists 68% of the time. This finding is consistent with studies conducted by the research team that developed the ODARA (Hilton & Harris, 2009; Hilton et al, 2004). However, a closer look at the univariate performance of each ODARA item revealed that items pertaining to the perpetrators’ history of acting violently toward others (i.e., Items 2 and 10) accounted for the majority of the ODARA’s prediction of further assault, whereas most other predictors added relatively little to the performance of the instrument.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Even with a relatively low base rate for physical assault recidivism, the ODARA total score was still able to accurately discriminate between recidivists and nonrecidivists 68% of the time. This finding is consistent with studies conducted by the research team that developed the ODARA (Hilton & Harris, 2009; Hilton et al, 2004). However, a closer look at the univariate performance of each ODARA item revealed that items pertaining to the perpetrators’ history of acting violently toward others (i.e., Items 2 and 10) accounted for the majority of the ODARA’s prediction of further assault, whereas most other predictors added relatively little to the performance of the instrument.…”
Section: Discussionsupporting
confidence: 91%
“…There is preliminary evidence suggesting that the ODARA is effective in categorizing the majority of eventual intimate partner homicide offenders into its highest risk category (Eke, Hilton, Harris, Rice, & Houghton, 2011). Hilton and Harris (2009) have also shown that the ODARA can distinguish between IPV recidivists and nonrecidivists within a sample of offenders with less extensive criminal records. A meta-analysis by Messing and Thaller (2013) identified that the ODARA had the best predictive accuracy of all the IPV risk instruments examined, with an average area under the curve (AUC) of .67 and a range of .64 to .72 (moderate to large effect sizes).…”
mentioning
confidence: 99%
“…As a result of new pro-arrest and mandatory arrest policies in the United States and Canada in the mid-1980s, the criminal justice system encountered an influx of intimate partner violence (IPV) offenders (Hilton & Harris, 2009). 1 As a response, U.S. courts began sentencing IPV offenders to community-based batterer intervention programs, wherein IPV offenders attend weekly group sessions to learn alternatives to violence.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that IPV is easier to prevent rather than treat; therefore, early intervention is a key mechanism in reducing and potentially eliminating IPV (Babcock, Green, & Robie, 2004; Hilton & Harris, 2009). Considering that the frequency of IPV has remained unchanged over the past decade (CDC, 2011b), more effective interventions that target both boys and girls during key development periods are needed (Chiodo, Crooks, Wolfe, McIsaac, Hughes, & Jaffe, 2012; O’Leary & Slep, 2012).…”
Section: Resultsmentioning
confidence: 99%